2010
DOI: 10.1016/j.biomaterials.2009.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Surfaces modified with nanometer-thick silver-impregnated polymeric films that kill bacteria but support growth of mammalian cells

Abstract: Silver is widely used as a biocidal agent in ointments and wound dressings. However, it has also been associated with tissue toxicity and impaired healing. In vitro characterization has also revealed that typical loadings of silver employed in ointments and dressings (∼ 100 μg/cm2) lead to cytotoxicity. In this paper, we report the results of an initial study that sought to determine if localization of carefully controlled loadings of silver nanoparticles within molecularly thin films immobilized on surfaces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
197
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 38 publications
5
197
0
4
Order By: Relevance
“…Moreover, other authors have reported that, as in our experiments, AgNPs sometimes had a proliferative effect. Agarwal et al (1) found that low non-toxic doses of nanosilver stimulated the growth of mouse fibroblasts NIH/3T3, while Rosas-Hernandes et al (26) observed the proliferative activity of nanosilver towards coronary endothelial cells (CEC), although in this case the effect was in reverse proportion to the applied concentration. In contrast, our results did not confirm the hypothesis by Arora et al (4) about lesser sensitivity of primary cell cultures to nanosilver.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other authors have reported that, as in our experiments, AgNPs sometimes had a proliferative effect. Agarwal et al (1) found that low non-toxic doses of nanosilver stimulated the growth of mouse fibroblasts NIH/3T3, while Rosas-Hernandes et al (26) observed the proliferative activity of nanosilver towards coronary endothelial cells (CEC), although in this case the effect was in reverse proportion to the applied concentration. In contrast, our results did not confirm the hypothesis by Arora et al (4) about lesser sensitivity of primary cell cultures to nanosilver.…”
Section: Discussionmentioning
confidence: 99%
“…6,33 During the short period of testing, NT and Ag-NT did not show any cytotoxicity to osteoblasts through direct contact. At 3 days, the number of cells on the surfaces of NT and Ag-NT were higher than that on Ti, which suggests that Ag-NT has no adverse effect toward osteoblasts, and may slightly promote their growth.…”
mentioning
confidence: 94%
“…Silver is effective against a broad spectrum of bacterial and fungal species, including strains that are resistant to antibiotics. 6 Silver nanoparticles are considered to be even more active due to their large surface area to volume ratio. 7 Previous work has indicated that silver nanoparticles embedded in titanium may be highly effective in inhibiting both Staphylococcus aureus and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the cytotoxicity and genotoxicity [4][5][6] of AgNPs raise risk for patient exposure. The cytotoxicity of AgNPs is directly proportional to the silver concentration, and 5-50 mg/ml AgNPs cause acute toxicity in rat liver cells (BRL 3A).…”
Section: Introductionmentioning
confidence: 99%